Heracleum kurdistanicum (Apiaceae; Tordylieae), a new subalpine species from Dalanpar Mountain, NW Iran - Tabad, Mohammad Aref; Maroofi, Hosein; Rastegar, Azad (Phytotaxa, 2021)
Heracleum kurdistanicum (Apiaceae; Tordylieae), a new subalpine species from Dalanpar Mountain, NW Iran, is described and illustrated. Heracleum kurdistanicum has no morphologically close relatives, but is compared with two most similar species: H. argaeum and H. schelkovnikovii. They differ in habit, leaves, fruits, and number and size of rays.